Peran Guru dalam Melaksanakan Evaluasi Pembelajaran di Sekolah - Patika Pratama; Windianti Windianti; Ira Susanti; Syahrial Syahrial (CV. Alim's Publishing, 2024)
This study's goal is to determine and examine the function that educators play in conducting learning assessments in classrooms. The methodology for this study was qualitative research with a literature study approach, or through literature study, which entails gathering data that is pertinent to the issue or topic under discussion and clarifies its significance. educators in the assessment of learning. This study focuses on educators who are involved in conducting assessments of student learning within educational institutions. The findings of this study demonstrate that, in the process of evaluating student learning, the teacher assumes the role of an evaluator, whose job it is to decide whether or not a teacher is effective in helping students learn. Or, to put it another way, assessment is what decides if a teacher is effective in helping students learn. Techniques and protocols employed in education must be maintained or improved.